2018
DOI: 10.3390/ijms19040956
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimmune Tau Mechanisms: Their Role in the Progression of Neuronal Degeneration

Abstract: Progressive neurodegenerative pathologies in aged populations are an issue of major concern worldwide. The microtubule-associated protein tau is able to self-aggregate to form abnormal supramolecular structures that include small oligomers up to complex polymers. Tauopathies correspond to a group of diseases that share tau pathology as a common etiological agent. Since microglial cells play a preponderant role in innate immunity and are the main source of proinflammatory factors in the central nervous system (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 97 publications
1
24
0
Order By: Relevance
“…In this context, this is where our theory of neuroimmunomodulation plays an important role and focuses on the link between neuronal damage and brain inflammatory process, mediated by the progressive activation of astrocytes and microglial cells with the consequent overproduction of proinflammatory agents (Maccioni et al, 2009). Despite clinical and pathological differences, increasing experimental evidence indicates that neuroinflammatory events lead to tau protein misfolding (Cortes et al, 2018).…”
Section: Neuroinflammation In Admentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, this is where our theory of neuroimmunomodulation plays an important role and focuses on the link between neuronal damage and brain inflammatory process, mediated by the progressive activation of astrocytes and microglial cells with the consequent overproduction of proinflammatory agents (Maccioni et al, 2009). Despite clinical and pathological differences, increasing experimental evidence indicates that neuroinflammatory events lead to tau protein misfolding (Cortes et al, 2018).…”
Section: Neuroinflammation In Admentioning
confidence: 99%
“…These neurodegenerative disorders (tauopathies) do not have a defined clinical, biochemical, and morphological characteristic, like other diseases. Neurodegenerative disorders are distinguished by accumulation of misfolded proteins, such as α-synuclein (α-syn) protein in Parkinson’s disease (PD) and tau protein in AD (Cortes et al, 2018). An important group of degenerative diseases are the so-called tauopathies, which consist in the pathological accumulation of tau protein in intracellular fibrillary aggregates.…”
Section: Neuroinflammation In Several Tauopathiesmentioning
confidence: 99%
“…To the best of our knowledge, no study has investigated whether specific tau isoforms differentially modulate immune responses. 3R and 4R tau were reported to differ in their physiological function and pathological role (68), and interplays between tau mechanisms and immune responses are thought to contribute to tau pathogenesis (71,72). We therefore hypothesized that increasing the abundance of 4R tau would impact on tau pathology as well as on behavioral and physiological responses to mild systemic inflammation induced by LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Altered immune status is a common feature of tauopathies (71,72), regardless of their classification in terms of 3R/4R predominance. To the best of our knowledge, no study has investigated whether specific tau isoforms differentially modulate immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Both events contribute to neuronal cell death and progressive damages to the brain tissue. Several studies have reported that chronic neuroinflammation related to the over-activation of microglia and astrocytes can accelerate tau hyperphosphorylation and Aβ aggregation via the overproduction of pro-inflammatory cytokines [ 40 , 41 , 42 ]. PD is another chronic and progressive neurodegenerative disease with the continuous loss of dopaminergic neurons, thereby inducing motor, cognitive, and neuropsychiatric dysfunction.…”
Section: Neuroinflammation and Cns Degenerative Diseasesmentioning
confidence: 99%